FORMATION OF MOTHER LANGUAGE COMPETENCES OF PRIMARY CLASS TEACHERS IN THE PROCESS OF PROFESSIONAL IMPROVEMENT - Nurmatova S. I.; Gaziyeva L. A. (Web of Journals Publishing, 2024)
The article talks about the formation of competences of primary school teachers in the subject of mother tongue in the process of professional development.
Keywords: professional development, process, primary education, teacher, mother tongue, competence.